2022
DOI: 10.3390/healthcare10010093
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation during the COVID-19 Pandemic among A Large-Scale Iranian Sample: The Roles of Generalized Trust, Insomnia, and Fear of COVID-19

Abstract: The novel 2019 coronavirus disease (COVID-19) is still not under control globally. The pandemic has caused mental health issues among many different cohorts and suicidal ideation in relation to COVID-19 has been reported in a number of recent studies. Therefore, the present study proposed a model to explain the associations between generalized trust, fear of COVID-19, insomnia, and suicidal ideation during the COVID-19 pandemic among a large-scale Iranian sample. Utilizing cluster sampling with multistage stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…HCWs have been repeatedly exposed to death and pain during the COVID-19 pandemic ( 67 ), and as postulated by Smith and Cukrowicz ( 68 ), constant exposure to pain and death may favor suicidal behavior and ideation. This may suggest that work environments where there is a higher risk of infection may favor a worsening of the mental health of particularly exposed HCWs ( 69 ). In this case, there is certain controversy as to the higher or lower prevalence of suicide rates among frontline HCWs compared to other types of workers.…”
Section: Discussionmentioning
confidence: 99%
“…HCWs have been repeatedly exposed to death and pain during the COVID-19 pandemic ( 67 ), and as postulated by Smith and Cukrowicz ( 68 ), constant exposure to pain and death may favor suicidal behavior and ideation. This may suggest that work environments where there is a higher risk of infection may favor a worsening of the mental health of particularly exposed HCWs ( 69 ). In this case, there is certain controversy as to the higher or lower prevalence of suicide rates among frontline HCWs compared to other types of workers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have examined the relationship between decreased trust and increased fear within the COVID-19 context [ 41 , 42 ]. Other studies have suggested increased perceived trustworthiness when people wear a face mask [ 43 ].…”
Section: Study 1—trustworthinessmentioning
confidence: 99%
“…SEM was evaluated using several goodness-of-fit indices. More specifically, the model fit was evaluated using fit indices of nonsignificant χ2, comparative fit index (CFI) > 0.90, together with standardized root mean square residual (SRMR) and the root mean square error of approximation (RMSEA) < 0.08 [ 66 , 67 , 68 , 69 , 70 , 71 ]. Furthermore, maximal and composite reliability were used to estimate the model’s validity.…”
Section: Methodsmentioning
confidence: 99%